Resilience in context: the association between neighborhood disadvantage and cumulative positive childhood experiences among justice-involved youth - Craig, Jessica M. (Crime & delinquency, 2021)
Alongside the research on the impact of cumulative trauma on later outcomes, scholars have started to investigate how an accumulation of protective factors may buffer adverse outcomes. However, these studies have failed to consider how one’s social context, in particular the levels of social disorganization and immigrant concentration present, may be associated with the accumulation of protective factors. Using data from the Florida Department of Juvenile Justice, the current study examines how both youth- and neighborhood-level factors predict cumulative positive childhood experiences (PCEs) among justice-involved youth. The results indicated that while immigrant concentration is unassociated with PCE accumulation, social disorganization is negatively associated with the number of PCEs, holding all else constant.